Development of DNA Biosensors Based on DNAzymes and Nucleases. (2nd January 2023) - Yang, Hualin; Peng, Yu; Xu, Mingming; Xu, Shuxia; Zhou, Yu
Abstract: DNA biosensors play important roles in environmental, medical, industrial and agricultural analysis. Many DNA biosensors have been designed based on the enzyme catalytic reaction. Because of the importance of enzymes in biosensors, we present a review on this topic. In this review, the enzymes were divided into DNAzymes and nucleases according to their chemical nature. Firstly, we introduced the DNAzymes with different function inducing cleavage, metalation, peroxidase, ligation and allosterism. In this section, the G-quadruplex DNAzyme, as a hot topic in recent years, was described in detail. Then, the nucleases-assisted signal amplification method was also reviewed in three categories including exonucleases, endonucleases and other nucleases according to the digestion sites in DNA substrates. In exonucleases section, the Exo I and Exo III were selected as examples. Then, the DNase I, BamH I, nicking endonuclease, S1 nuclease, the duplex specific nuclease (DSN) and RNases were chosen to illustrate the application of endonucleases. In other nucleases section, DNA polymerases and DNA ligases were detailed. Last, the challenges and future perspectives in the field were discussed.